How do high performance work systems influence organizational innovation in professional service firms? - Fu, Na; Flood, Patrick C; Bosak, Janine; Morris, Tim; O'Regan, Philip (Employee relations, 2015)
Purpose – The purpose of this paper is to examine how a system of human resource management (HRM) practices, labelled high-performance work systems (HPWS), influences organizational innovation in professional service firms (PSFs). In this study, innovation in PSFs is seen as an indicator of firm performance and is calculated as the revenue per person generated from new clients and new services, respectively. Design/methodology/approach – Quantitative data were collected from 195 managing partners, HR managers or experienced Partners in 120 Irish accounting firms. Hierarchical regression analysis was used to test the hypotheses. Findings – The analysis results indicate strong support for the mediating role of employees’ innovative work behaviours in the relationship between HPWS and two types of PSFs’ innovation performance. Practical implications – Managers need to effectively adopt and implement innovation-based HRM practices to encourage and support employees’ creative thinking and innovation. Through the adoption and utilization of these practices managers can enhance the firm’s innovation and its performance. Originality/value – This study contributes to our understanding of the link between HRM and firm innovation by explicating a pathway between these variables. This study also generalizes consistent findings on the HRM-firm innovation relationship to a different context, i.e. PSFs.